ANALISIS PENERAPAN PASAL 127 TUNGGAL TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DALAM UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI DI DIREKTORAT RESERSE NARKOBA KEPOLISIAN DAERAH SUMATERA UTARA) - Albret Duvry; Adi Mansar (JURNAL DOKTRIN REVIEW, 2023)
Narcotics abuse in Indonesia has reached the stage of concern, the problems raised are how the procedure for implementing rehabilitation for narcotics offenders, how to apply a single Article 127 to narcotics offenders, how the efforts of the Poldasu Narcotics Investigation in providing rehabilitation for narcotics offenders. The research method used is normative juridical research, Police Investigation Procedures qualify perpetrators as dealers and perpetrators as Narcotics abusers based on the investigative mechanism up to the filing of cases, based on mandated requirements with provisions related to rehabilitation, namely from the amount of evidence, an assessment is carried out by the Integrated Assessment Team formed by BNN. Single application of Article 127 When narcotics addicts or abusers are caught red-handed,evidence of narcotics is found in accordance with SEMA provisions No: 4 of 2010 concerning Placement, Abuse, Victims of Abuse and Narcotics Addicts into Medical and Social Rehabilitation Institutions. The effort made is discretion. To exercise discretion, the investigator examines witnesses, potential suspects, tests evidence and urine to the laboratory. After that, conduct a case title and determine the status as a suspect Article 127 paragraph 1 letter a JO Article 54 of the Narcotics Law JO Article 55 Paragraph (1) 1 of the Criminal Code in connection with fulfilling the elements of Articles 183 and 184 of the Criminal Procedure Code